Pengaruh Profitabilitas, Leverage, Komisaris Independen, Kepemilikan Institusional, dan Ukuran Perusahaan terhadap Penghindaran Pajak pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2014-2018 - Novita Sari; Elvira Luthan; Nini Syafriyeni (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The biggest source of state income comes from taxes. So the Indonesian government continues to strive to improve tax revenue optimization measures to maximize revenue from the tax sector. But until now many citizens still consider tax as a burden. The company or entity still considers tax as an expense that will reduce the company's net profit. Taxpayers will tend to look for ways to reduce the tax they pay, both legally and illegally, one of which is the practice of tax avoidance Tax avoidance is a complex and unique problem because on one hand tax avoidance does not violate the law, on the other hand tax avoidance is not wanted by the government because it reduces income for the country. The purpose of this study is to analyze the effect of profitability, leverage, the proportion of independent commissioners, institutional ownership, and company size, on tax avoidance. The population of this research is the entire manufacturing company registered in indonesia stock exchange (BEI ) 2014-2018 during the period.A method of sampling nonprobability using methods with techniques of sampling purposive sampling .The technique of analysis of data using the test is the classic normality, multikolinieritas,  heteroskedastisitas test, and autokorelasi  test. Testing the hypothesis of the use of regression analysis double. The results of the study show that there is an influence between profitability and the proportion of independent commissioners on tax avoidance, while the variable leverage, institutional ownership and firm size do not show an influence on tax avoidance.